2018
DOI: 10.3389/fnhum.2017.00662
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Functional Connectivity of the Contra- and Ipsilateral Secondary Somatosensory Cortex during Tactile Object Recognition

Abstract: In the somatosensory system, it is well known that the bilateral secondary somatosensory cortex (SII) receives projections from the unilateral primary somatosensory cortex (SI), and the SII, in turn, sends feedback projections to SI. Most neuroimaging studies have clearly shown bilateral SII activation using only unilateral stimulation for both anatomical and functional connectivity across SII subregions. However, no study has unveiled differences in the functional connectivity of the contra- and ipsilateral S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Specifically, DMN with its areas MPFC, PCC, Angular Gyrus, and medial temporal lobe structures plays and important role in monitoring self-referential mental activity; the SN through ACC and Insula, receives and elaborates body sensations and cognitive relevant events engaging frontoparietal systems; CEN, whose key nodes include the dorsolateral prefrontal cortex (DLPFC) and PCC, maintains and elaborates working memory information and decision-making of goal-directed behavior. These networks interact dynamically, mediating cognitive and emotional states (Yu et al, 2018). The SN (Seeley et al, 2007) is involved in bottom-up direction of salience events, involved in detecting, integrating and filtering relevant interoceptive, autonomic and emotional information, and it plays a key role modulating and switching other resting state networks (Menon and Uddin, 2010).…”
Section: Wilfred Ruprecht Bion: the Theory Of “Alpha Function”mentioning
confidence: 99%
“…Specifically, DMN with its areas MPFC, PCC, Angular Gyrus, and medial temporal lobe structures plays and important role in monitoring self-referential mental activity; the SN through ACC and Insula, receives and elaborates body sensations and cognitive relevant events engaging frontoparietal systems; CEN, whose key nodes include the dorsolateral prefrontal cortex (DLPFC) and PCC, maintains and elaborates working memory information and decision-making of goal-directed behavior. These networks interact dynamically, mediating cognitive and emotional states (Yu et al, 2018). The SN (Seeley et al, 2007) is involved in bottom-up direction of salience events, involved in detecting, integrating and filtering relevant interoceptive, autonomic and emotional information, and it plays a key role modulating and switching other resting state networks (Menon and Uddin, 2010).…”
Section: Wilfred Ruprecht Bion: the Theory Of “Alpha Function”mentioning
confidence: 99%
“…Studies on macaque monkeys shown that tactile stimuli can be distinguished based on their temporal features, which are fundamental for vibrotactile frequency perception (Harvey, Saal, Dammann, & Bensmaia, 2013; Mackevicius, Best, Saal, & Bensmaia, 2012). The temporal structures of tactile stimuli are important components in human judgments of surface texture and object recognition (Yang et al, 2017; Yu, Yang, Ejima, Fukuyama, & Wu, 2017). Human behavioral studies found tactile frequency perception was similar to auditory frequency perception, in which the duration of silent gap between successive bursts was more important than underlying periodicity (Birznieks & Vickery, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We used two-dimensional (2-D) raised angles that had been employed in previous studies (Wu et al 2010; Yang et al 2014; Yu et al 2018). These angles were composed of plastic lines (8.0 mm long, 1.5 mm wide, and 1.0 mm high) and plastic square bases (40.0 mm long and wide, 3.0 mm high).…”
Section: Methodsmentioning
confidence: 99%
“…To address the questions mentioned above, we applied the tactile angle discrimination (AD) task used in our previous studies (Wu et al 2010; Yang et al 2014; Yu et al 2018). The AD task measures spatial perception of touch involving advanced cognition, such as WM and attention.…”
Section: Introductionmentioning
confidence: 99%